Some New Results for Certain Subclasses of Normalized Analytic Functions - Jadhav S.S (Mathematical Statistician and Engineering Applications, 2022)
In this Paper we define new subclasses of normalized regular functions namely (t, p,?). Some examples for the functions in (t, p,?) are also discussed. With certain condition we find the maximum radius in unit disc for which functions in the subclass (0, p,?) to be in Y ((?+1+|p|) 2).